'Pro-tobacco propaganda': a case study of tobacco industry-sponsored elementary schools in China. Issue 4 (13th July 2019) - Fang, Jennifer; Yang, Gonghuan; Wan, Xia
Abstract : Background: China is the largest producer and consumer of tobacco products worldwide. While direct marketing and advertisement of tobacco products is restricted, indirect marketing still exists under the guise of sponsorship and corporate social responsibility (CSR). This case study is focused on tobacco industry-sponsored elementary schools in Chinese rural areas. Methods: Field visits were conducted in Yunnan province to interview students, teachers, school principals and parents to understand their perceptions of the tobacco industry and its sponsorship of schools. Interviews with tobacco control activists were conducted in Beijing to discuss national tobacco control efforts targeting tobacco industry sponsorship. Interview data were transcribed and coded, with key themes developed using thematic analysis. Results: While health consequences of smoking are generally known, attitudes towards the tobacco industry and its CSR activities remain positive among the general public. Educators and parents do not perceive any impacts on schoolchildren from exposure to 'pro-tobacco propaganda' created by the industry's CSR activities. Attitudes among tobacco control activists were drastically different, with consensus that CSR activities constitute indirect marketing attempts that should be banned. Conclusion: National tobacco control legislation banning all forms of indirect marketing including CSR is needed in order to protect the health of future generations.